PSIKOEDUKASI PERILAKU ASERTIF UNTUK MENINGKATKAN KETERAMPILAN SOSIAL SISWA MIS TARBIYATUS SIBYAN - Azizah, Maryam Berda; Nurhidayah, Siti; Khoiriyah, Ummi (Universitas Islam 45 Bekasi, 2024)
Humans are required to have social skills so they can be part of a group, social problems arise in students' daily lives, for example individualistic attitudes. After conducting observations at MIS Tarbiyatus Sibyan, it was found that some students tended to be passive. Community Service Activities are carried out at MIS Tarbiyatus Sibyan. The aim is to provide an understanding of social skills and understand the benefits of assertive behavior on the social skills of MIS Tarbiyatus Sibyan students. The method used in Community Education is Psychoeducation. Participants in service activities were 40 students consisting of class 5 and class 6. Psychoeducation activities consisted of 6 stages, namely; (1) Observation, (2) Program Planning, (3) Program socialization to schools and pretest, (4) Psychoeducation on social skills & assertive behavior, (5) Evaluation (Posttest). The achievement indicator consists of 2 parts (1) Dare to say the 4 magic words honestly and without hurting. (2) Dare to express feelings of sadness, anger, joy, fear of yourself and others. As a result of the service activities, participants can carry out assertive behavior by exemplifying the 4 Magic Words according to appropriate situations and participants can practice the 4 types of emotions well.